2016
DOI: 10.1017/pab.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Herbivorous dinosaur jaw disparity and its relationship to extrinsic evolutionary drivers

Abstract: Morphological responses of nonmammalian herbivores to external ecological drivers have not been quantified over extended timescales. Herbivorous nonavian dinosaurs are an ideal group to test for such responses, because they dominated terrestrial ecosystems for more than 155 Myr and included the largest herbivores that ever existed. The radiation of dinosaurs was punctuated by several ecologically important events, including extinctions at the Triassic/Jurassic (Tr/J) and Jurassic/Cretaceous (J/K) boundaries, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 50 publications
5
36
2
Order By: Relevance
“…; Hopkins ; Maclaren et al . ; Romano ) have shown similar results, but more or less strongly. On the other hand, Mongiardino Koch et al .…”
supporting
confidence: 53%
“…; Hopkins ; Maclaren et al . ; Romano ) have shown similar results, but more or less strongly. On the other hand, Mongiardino Koch et al .…”
supporting
confidence: 53%
“…As such, the separation of the ‘Norian-Rhaetian’ and ‘Early Jurassic’ morphospaces observed in our PCoA results cannot be attributed to the phylogenetic position of the taxa within each time interval (Figs 13 and 14). Thus, one possible explanation for this splitting is that changes in the vegetation across the Triassic/Jurassic boundary [49,50] leaded to the shift in morphology seen in the jaw feeding apparatus of Norian-Rhaetian to Early Jurassic taxa (but see [51]–in that study, the results of morphological and biomechanical disparity analyses of the mandible of sauropodomorphs shows an overlap in the morphospace associated with Late Triassic and Early Jurassic taxa). As for the phylogenetic groupings, features of non-anchisaurian massopods such as Coloradisaurus and Yunnanosaurus huangi , which also has a dentition markedly different from that of its closest relatives [52], contribute to the great morphospace range occupied by that assemblage of sauropodomorphs (Fig 14).…”
Section: Discussionmentioning
confidence: 98%
“…Further analyses upon evolutionary trends in sauropodomorph cranial feeding adaptations are still ongoing. MacLaren et al () showed that the disparity of mandibular shape is in line with diversity of herbivorous dinosaur taxa, which increased throughout the Mesozoic. According to their study, biomechanical disparity peaks with increased variation in sauropods in the Late Jurassic, but then decreases thereafter in the Cretaceous.…”
Section: Discussionmentioning
confidence: 99%